How Much Do They Know? An Analysis of the Accuracy of HIV Knowledge among Youth Affected by HIV in South Africa - De Wet, Nicole (J Int Assoc Provid AIDS Care, 2019)
HIV/AIDS prevalence rates in South Africa are among the highest in the world. The key to reducing transmission is the dissemination of accurate knowledge. Here, we investigate the accuracy of HIV/AIDS knowledge among youth affected by the disease. Data from the Fourth South African National HIV, Behaviour and Health Survey (2012) are used and a weighted sample of 4 095 447 youth (15-24 years old) who have known or cared for someone with HIV/AIDS are analyzed. Results show that more than one-third (40.37%) of youth in South Africa are affected by the disease. One-quarter of the affected youth have 75% accurate knowledge of the virus, while only 10% have 100% accurate knowledge. Rural place of residence (odds ratio [OR] = 0.61) and looking for work (OR = 0.39) are less likely to have accurate knowledge. Youth without disabilities (OR = 2.46), in cohabiting (OR = 1.69), and in dating (OR = 1.70) relationships are more likely to have accurate knowledge. In conclusion, in order to reduce HIV incidence and combat HIV myths, efforts to improve the accuracy of HIV knowledge among youth affected by the disease are needed. There should be more community-based campaigns to target unemployed youth in the country.